Fluctuations of ice cover and sea water pressure nearby the Tunabreen Glacier front at Spitsbergen - S. V. Muzylev; Yu. Ya. Macheret; E. G. Morozov; I. I. Lavrentiev; A. V. Machenko (Лëд и снег)
Results of oceanographic measurements carried out in February, 2011, from the sea ice surface in the Tempelfjorden near the Tunabreen front in Svalbard are presented. Two temperature and pressure recorders SBE-39 were deployed on a wire from the ice approximately 300 m from the glacier front. The sampling time interval was 1 s. A pressure recorder SBE-37 was located under them on the bottom with a sampling interval of 6 s. Pressure oscillations on the bottom with a period of 90 s and ice cover oscillations with periods of 10 s and 14 s were recorded. The conclusion is made that the recorded oscillations of pressure in the sea water are related to the glacier microsurges, and the observed profiles of temperature, density, and salinity show the absence or insignificant inflow of fresh water from the glacier in the fjord during the winter season. The measurements allowed us to estimate the Young's modulus of the ice.